2015
DOI: 10.1074/jbc.m115.679019
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of the ISWI Chromatin Remodeling Complex of the Early Branching Eukaryote Trypanosoma brucei

Abstract: Background: Eukaryotes typically encode a range of ISWI chromatin remodeling complexes with different functions.Results: We have identified and analyzed three novel ISWI partners in the early branching eukaryote Trypanosoma brucei.Conclusion: T. brucei appears to have a single major ISWI complex.Significance: This unusually simple ISWI configuration could be a consequence of the relative lack of transcriptional regulation in this ancient eukaryote.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 85 publications
2
37
0
Order By: Relevance
“…Knockdown of histone H3 variant (H3V) or bromodomain factor 3 (BDF3) results in transcription of ESs and subtelomeric array VSGs, whereas BDF2 null cells transcribe VSG genes from silent ESs (12,34). Knockdown of the ISWI chromatin remodeling complex, which is enriched at ES promoter regions, rRNA loci, and SSRs, also affects transcription of silent ESs but not of VSG genes (11,35). PIP5Pase may have functional associations with some of these proteins, which control transcription of VSG genes from ESs and subtelomeric arrays, as some of these proteins were also found to interact with PIP5Pase and/or RAP1 (discussed below).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of histone H3 variant (H3V) or bromodomain factor 3 (BDF3) results in transcription of ESs and subtelomeric array VSGs, whereas BDF2 null cells transcribe VSG genes from silent ESs (12,34). Knockdown of the ISWI chromatin remodeling complex, which is enriched at ES promoter regions, rRNA loci, and SSRs, also affects transcription of silent ESs but not of VSG genes (11,35). PIP5Pase may have functional associations with some of these proteins, which control transcription of VSG genes from ESs and subtelomeric arrays, as some of these proteins were also found to interact with PIP5Pase and/or RAP1 (discussed below).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a histone H3 variant, a bloodstream stagespecific modified DNA base known as J or hydroxymethyluracil (22,23), the chromatin remodeling ISWI complex (24), the histone H3K76 trimethyltransferase DOT1B (25), and the telomere-associated protein RAP1 (26) all facilitate VSG-ES silencing. In addition, cohesin function facilitates maintenance of the active VSG-ES (27), and inositol phosphate signaling impacts VSG-ES regulation (28).…”
mentioning
confidence: 99%
“…Up to now, transcriptional control seemed to be no relevant in trypanosomes. However, recently, several reports implicated various proteins in RNA Pol I and Pol III transcription regulation (Romero-Meza et al 2017;Stanne et al 2015), while little is known about the factors involved in transcriptional regulation of Pol II-driven genes. Interestingly, it has been shown that the spatial position of genes within a PTU can have a major impact in the control of gene expression.…”
Section: Discussionmentioning
confidence: 99%